Sliding mode controller with fuzzy supervisor for MPPT of photovoltaic pumping system - Taleb Hamdi; Khaled Elleuch; Hafedh Abid; Ahmed Toumi (Institute of Advanced Engineering and Science, 2023)
This paper focuses on a photovoltaic system for pumping water. The control strategy for this water pumping system is based on Takagi-Sugeno type fuzzy supervisors and sliding mode controller. The first generates the maximum power point current under varying climatic condition whereas the second allows tracking the reference signal produced by the fuzzy supervisor. The system includes a photovoltaic generator (PVG) followed by a DC-DC Converter, DC bus, an AC/DC inverter which is connected to the induction motor. This latter is coupled with a centrifuge pump. The induction motor is driven based on field-oriented control strategy. The Takagi-Sugeno type fuzzy supervisor predicts, depending on the variations of climatic variables such as irradiation and temperature, the optimum operating point for the photovoltaic source. The simulation results show the effectiveness of the proposed approach in transient and stationary regimes for different values of climatic variables.